Assessment of the potential carbon footprint of engineered processes for the mineral carbonation of PGM tailings - Ncongwane, Mpendulo S (Department of Chemical Engineering, 2016)
Mineral carbonation is a carbon sequestration technology that entails the reaction of CO2 with oxides or silicates of magnesium, calcium or iron to produce stable carbonate compounds. Magnesium-rich tailings from the platinum industry in South Africa have been identified as a potentially viable and attractive feedstock for CO2 sequestration through mineral carbonation. Many of the strategies proposed to enhance the dissolution kinetics of silicate minerals, such as the use of elevated temperatures and pressures and chemical additives, as well as pretreatment through mechanical and thermal activation, are energy intensive and will thus reduce the net CO2 sequestration capacity of the overall mineral carbonation process. As a result, there is growing recognition of the need to evaluate the processes using life-cycle based approaches and tools to ensure they result in net CO2 reduction. However, to date, research and development has focused primarily on the optimisation of extraction and/or carbonation efficiencies, with specific emphasis on the relatively reactive silicate minerals, such as olivine and serpentine. This project seeks to investigate the viability of using pyroxene-rich PGM tailings for the sequestration of CO2, with specific emphasis on net carbon neutrality. Promising mineral carbonation processes have been identified on the basis of an extensive literature review, and include the: ammonium salts pH swing, Lackner's HCl multi-stage, gas-solid Abo Akademi University process, direct aqueous process, and mineral acid pH swing. Material and energy balances were then conducted for these processes on the basis of the sequestration of 1 ton of carbon dioxide, using Aspen Plus v8 simulation software package. The material and energy data were then used to determine the total carbon footprint contributions, through the use of SimaPro v 7.7.3. life cycle assessment software.